The burden of ethics: the use of design and architecture as political propaganda - Muratovski, G (Popular Culture Association of Australia and New Zealand (POPCAANZ), 2014)
In the face of an underlying theoretical structure that links the subjects of propaganda and politics with architectural and design practice, it can be argued that both designers and architects often use ideologies (self-invented or borrowed) to shape their communicative and design processes. It is their beliefs and dialogues that condition what ideals may lead to a better society and how these ideals can be put into practice—often for the benefit or to the detriment of the society at large. In most cases, these practices are juxtaposed with moral and ethical issues that are too great to be ignored.
Keywords: Politics; Ethics; Design; Architecture; Propaganda